2020
DOI: 10.1186/s43066-020-00033-z
|View full text |Cite
|
Sign up to set email alerts
|

The association between vitamin D status and non-alcoholic fatty liver disease in adults: a hospital-based study

Abstract: Background: The association between vitamin D levels and non-alcoholic fatty liver disease (NAFLD) has been increasingly determined in recent researches. The aim of this study was to determine the association between vitamin D levels, measured as serum 25-hydroxy vitamin D (25(OH)D) and NAFLD. Serum 25(OH)D was prospectively determined in 80 patients. Of them, 40 subjects had NAFLD, whereas 40 subjects served as healthy control. Vitamin D deficiency was defined as serum 25(OH)D level < 20 ng/ml. Receiver opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…A higher cutoff point ≤40 had 77.17% sensitivity and 89.36% specificity of predicting NAFLD, AUC 0.749 and p < 0.000 in a previous study [27]. Another recent study revealed a much lower cutoff point, where serum 25(OH)D level of <11.2 ng/ml increases the risk of NAFLD with 45% sensitivity and 97.5% specificity [26].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A higher cutoff point ≤40 had 77.17% sensitivity and 89.36% specificity of predicting NAFLD, AUC 0.749 and p < 0.000 in a previous study [27]. Another recent study revealed a much lower cutoff point, where serum 25(OH)D level of <11.2 ng/ml increases the risk of NAFLD with 45% sensitivity and 97.5% specificity [26].…”
Section: Discussionmentioning
confidence: 86%
“…Theories include the lack Vitamin D anti-inflammatory and antifibrotic effect on hepatic stellate cells. As Vitamin D decreases peripheral and hepatic insulin resistance induced by free fatty acids, VDD could be associated with increased accumulation of lipids in the liver and hence NAFLD development [26].…”
Section: Discussionmentioning
confidence: 99%
“…The potent immunosuppressive effects of 1,25(OH) D 3 indicate its function in preventing preeclampsia in pregnancy [ 4 ]. Researchers postulated that, as a result of such events in utero environment, foetal programming induces specific genes and genomic pathways that control foetal development and subsequent disease risk [ 5 ]. Therefore, prenatal vitamin D deficiency may not only affect maternal skeletal preservation and foetal skeletal formation but also influence foetal “imprinting” that may affect chronic disease susceptibility postnatally [ 3 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Кроме того, выявлены корреляции между снижением 25(ОН)D сыворотки крови и повышением индекса массы тела (ИМТ), увеличением окружности талии, отношения окружности талии к окружности бедер, повышением уровня триглицеридов [11,12]. Имеются данные, что витамин D может контролировать артериальное давление через регулирующее влияние на ренин-ангиотензин-альдостероновую систему [13], улучшать состояние сердечно-сосудистой системы [14], снижать активность аутоиммунных процессов в организме [15], ингибировать прогрессирование неалкогольной жировой болезни печени [16]. Установлены ассоциативные связи между низким уровнем витамина D и риском онкопатологии [17].…”
Section: таблица 1 характеристики групп женщин с сд 1-го и 2-го типа включенных в исследованиеunclassified